(3QSGdI aj HYV GdabgGA hGdbVGI GdeZGQHI hJGQjN ehJge hPcQ eQV HYVge hOafge hGdJYQja HbHhQges - (3eMeO Hf Ydj Hf GdMSf Hf HTQ, CHh YHO Gddg, GdMcje GdJQePj , J (B320 (3g` s
(3ChdgG (B:s
(3Yf Gdabjg eMeO Hf HdbGSe GdMSfi ,GdeJhai SfI (B988(3g` s
(3BNQgG (B:s
(3Yf GdabjI EHQGgje Hf eMeO GdTGhj , GdeJhai SfI (B1005(3g` s
(3Vef eLehY , JQJjHgG (B: (3ef U (B425 - (3U(B426s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B4 - (3U (B199 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdRGhjI GdMeRGhjI (B(80) s
Keywords: (3GdJGQjNs